COMPARISON OF CORONARY PROGNOSTIC INDEX VS CLINICAL MARKERS OF REPERFUSION IN ACUTE CASES OF MYOCARDIAL INFARCTION - ANDHALE, AMOL; VARMA, ANUJ; ACHARYA, SOURYA; KUMAR, SUNIL (International Journal of Psychosocial Rehabilitation, 2020)
For the treatment of myocardial infarction with ST-segment elevation, primary angioplasty is considered superior to fibrinolysis for patients who are admitted to hospitals with angioplasty facilities. Whether this benefit is maintained for patients who require transportation from a community hospital to a centre where invasive treatment is available is uncertain so primary thrombolysis is frequently successful at restoring coronary artery blood flow in patients with acute ST-segment–elevation myocardial infarction.To evaluate prognostic index in patients of AMI, To evaluate clinical markers of reperfusion after thrombolysis.To correlate coronary prognostic index and clinical markers of reperfusion in AMI in relation to early morbidity & mortality.To evaluate prognostic index in patients of AMI To evaluate clinical markers of reperfusion after thrombolysis. To correlate coronary prognostic index and clinical markers of reperfusion in AMI in relation to early morbidity & mortality. To evaluate prognostic index in patients of AMI To evaluate clinical markers of reperfusion after thrombolysis. To correlate coronary prognostic index and clinical markers of reperfusion in AMI in relation to early morbidity & mortality.Clinical assessment every half hour for 2 hrs. will be done to assess:Reduction in chest pain in percentage on a subjective scale & to assess any change in Killip’s class. Continuous ECG monitoring to observe occurrence of reperfusion arrhythmias. At the end of 2 hrs. of follow up patients will be evaluated for: Percentage reduction in chest pain on subjective scale A twelve lead ECG to detect any change in ST elevation.Repeat serial estimation of CKMB. Successful clinical reperfusion is defined as presence of two of the following criteria at 2 hrs. of starting treatment. Chest pain evolution: Pain intensity will be quantified by percentage reduction in chest pain on subjective basis. A succdssfull pain criterion is defined as 50% or more reduction in chest pain intensity at 2 hours after starting thrombolysis. ST segment elevation: A decreased 50% or more in summations of ST segment elevation is considered a positive electrocardiographic criteria. Enzyme evolution: A positive enzymatic criteria is define as, more than two times increase over upper normal limits or base line values. At the end of two hours of starting thrombolysis patients will be divided in to two groups based on SCR positive or negative. Successful reperfusion will be grouped into SCR positive group and without successful reperfusion SCR (negative) group.ResultsThe successful clinical reperfusion in the present study was 61% while 39% patients did not have successful clinical reperfusion. It is come to an end that Killip’s class at admission of ≥ 2 and absence of successful clinical reperfusion were predictors of mortality after thrombolysis. Mortality rate was more in patients without successful clinical reperfusion than in patients with successful clinical reperfusion. It is further advocated that all patients of acute myocardial infarction who receive thrombolysis should be examined at the end of 2 hours for these simple, non invasive clinical markers of reperfusion. Absence of successful clinical reperfusion group of patients with poorer prognosis after thrombolysis and in such patients alternative strategies of reperfusion should be considered.